Comprehensive Study of Health Education Strategies for Diverse Populations - Alswidan, Abdullah Moslah Hamad; Alghasham, Eman Ameer; Almarhoun, Mohannad Mohammed; Al Zaid, Hussain Jassim; Al Suliman, Abdullah Hamad Shagath; Al sawadan, Ali Mosleh Hamad; Alswiadan, Hamad Mosleh Hamad; ALswedan, Ali Yahya Fhaed (Journal of Ecohumanism, 2024)
Community health education promotes health, decreases inequity, and establishes health-promoting societies. According to the latest data, the focus is being made on the development of specific health education approaches to meet the needs of various target groups related to culture, language, and income level. This paper investigates various health education approaches in terms of their impact on different target groups and the difficulties and achievements encountered in the practice of the selected strategies in various contexts of healthcare delivery. The study considers the need to develop culturally sensitive health education programs and use the right instruments, means, and modes of transmitting the information. It also reviews community participation, using material from high to simple levels, and incorporating environmental factors into health education.